Current status of outcome measures in vasculitis: focus on Wegener's granulomatosis and microscopic polyangiitis. Report from OMERACT 7. - Merkel, P; Seo, P; Aries, P; Neogi, T; Villa-Forte, A; Boers, M; Cuthbertson, D; Felson, D; Hellmich, B; Hoffman, G; Jayne, DR; Kallenberg, C; et al. (2005)
The complexity of assessing disease activity, disease status, and damage in the vasculitides reflects the multisystemic pathologic manifestations of these often chronic illnesses. Major progress has been made in the past decade in the development of validated and widely accepted outcome measures for use in clinical trials. Over time, these tools have been regularly revised, expanded, and supplemented with new measures of disease prognosis and damage. As a result clinical research in this area has become increasingly complex. This article critically reviews the current status of tools for assessing disease activity and damage in "ANCA-associated" vasculitides (Wegener's granulomatosis and microscopic polyangiitis), summarizes the current level of validation of each measure, addresses central problems and controversies to be considered during development of new vasculitis assessment tools, and proposes a series of research agendas for consideration by the vasculitis research community.